A curtailed task for quantitative evaluation of visuomotor adaptation in the head-mounted display virtual reality environment - Chang, Huiyeong; Woo, Sung-Ho; Kang, Sura; Lee, Chan Young; Lee, Jee-Young; Ryu, Jeh-Kwang (Frontiers in Psychiatry, 2023)
To accurately perform a goal-directed movement in continuously changing environments, it is unavoidable for individuals to adapt accordingly. The cerebellum has been known to be responsible for such process, specifically adaptation using sensorimotor information. As shown in previous studies, using HMD-VR technology in an experimental setting has similar advantages as in the real-world environment: researchers can manipulate the experimental environment, precisely control the experiments, and analyze errors quantitatively in real time. Moreover, the HMD-VR environment provides high immersiveness and embodiment which even enhance motor learning and increase engagement and motivation of individuals more than real-world environments do. In our HMD-VR-based task, the subjects were trained to adapt to a condition in which the visual information was artificially 20° clockwise rotated from the actual cursor movement. The subjects used a virtual reality tracker to move the cursor from a starting point to a target that appeared randomly at five locations at interval of 15° and a radius of 20cm from the starting point. Although no significant side effects were expected from experiencing the HMD-VR environment, we considered the appropriate number of trials given to patients with cerebellar disease, who have difficulty with visuomotor adaptation, for future use in clinical settings. To examine the feasibility of our HMD-VR task for analysis of visuomotor adaptation pattern as shown in a real-world task, we created two paradigms with a difference in the number of trials. As we expected, the results showed that the heading angle error gradually decreased as the participants of both groups continued the task. Based on the between-group comparison and within-group comparison results, no significant difference was found between two paradigms. These observations showed that our short task paradigm is feasible for analysis of visuomotor adaptation. Next, we applied this task to patients with cerebellar atrophy and age-matched controls for further examination of applicability to diagnosis and rehabilitation of the patients. As a result, we observed the distinguishable adaptation pattern of the patient group by using our paradigm. Overall, the results suggest that our paradigm is feasible to analyze the visuomotor adaptation pattern so may contribute to the clinical field.